Pengaruh Perendaman Benih dengan Beauveria Bassiana pada Beberapa Lama Simpan terhadap Pertumbuhan Bibit Kakao - Endah Cahyani Simamora; Nantil Bambang Eko Sulistyono; Indah Anita Sari (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2026)
Cocoa is recalcitrant seed which it has the high water content and the deterioration goes quickly. The distribution of cocoa seed need longer time and it will decrease the quality of cocoa seed and cocoa seedling. The research aimed to determine of effectiveness seed soaking with Beauveria bassiana after storage during the distribution of seed. This research was conducted in Indonesian Cofee and Cocoa Research Institute. The research was conduct using randomized complete block design with a factorial arrangement. First  factor was the  storage period  of two days (L2), three days (3 hari), four days (L4), five days (L5), six (L6) and seven days (L7). The second factor was seed soaking with Beauveria bassiana (B1) and seed soaking with fungicide (B0). The result showed that storage periode had significant effect on  plant height and stem diameter. Seed soaking with Beauveria bassiana showed significant effect on plant height. The interaction between storage periode and seed soaking with Beauveria bassiana had no significant effect on the height of seedling, stem diameter and leaf number of seedling.